2012
DOI: 10.1158/0008-5472.can-11-1628
|View full text |Cite
|
Sign up to set email alerts
|

Role of JNK in Mammary Gland Development and Breast Cancer

Abstract: JNK signaling has been implicated in the developmental morphogenesis of epithelial organs. In this study we employed a compound deletion of the murine Jnk1 and Jnk2 genes in the mammary gland to evaluate the requirement for these ubiquitously expressed genes in breast development and tumorigenesis. JNK1/2 was not required for breast epithelial cell proliferation or motility. However, JNK1/2 deficiency caused increased branching morphogenesis and defects in the clearance of lumenal epithelial cells. In the sett… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 52 publications
3
78
0
Order By: Relevance
“…Compound JNK deficiency in epithelial cells of the prostate (this study), breast (2), and liver (9) causes an increase in carcinogenesis. This observation suggests that JNK may act to reduce tumor development in these epithelial tissues.…”
Section: Jnk and Pten Cooperate To Regulate The Development Of Invasivementioning
confidence: 89%
See 3 more Smart Citations
“…Compound JNK deficiency in epithelial cells of the prostate (this study), breast (2), and liver (9) causes an increase in carcinogenesis. This observation suggests that JNK may act to reduce tumor development in these epithelial tissues.…”
Section: Jnk and Pten Cooperate To Regulate The Development Of Invasivementioning
confidence: 89%
“…These transcription factors represent an important component of the immediate-early gene response to mitogens and inflammatory stimuli (2). AP1 transcription factors are also implicated in dysregulated growth and tumor development (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, paradoxically, studies have demonstrated both a protumorigenic (16,41,42) and a tumor- (43,44) role for the JNK family, with duration of activation and context both implicated in defining the response (45). A major consideration in addressing these contrasting results is that reports of JNK acting as a tumor suppressor have studied the formation of primary tumors (46)(47)(48), where JNKmediated activation of apoptosis has an inhibitory role. In contrast, the in vivo screen described here represents an advanced tumor setting and our functional analyses confirm the complex interplay of prosurvival and proapoptotic signaling via JNK, which has important implications for the use of JNK inhibitors as potential therapeutics in cancer (12).…”
Section: Discussionmentioning
confidence: 99%